Curb your enthusiasm. The complete third season - Weide, Robert B.; David, Larry; Hines, Cheryl; Garlin, Jeff, 1962- (Burbank, CA : Warner Home Video, 2005)
Blending fact with fiction, a television series about "Seinfeld" co-creator Larry David.
Chet's shirt -- The Benadryl brownie -- Club soda and salt -- The nanny from hell -- The terrorist attack -- The special section -- The corpse-sniffing dog -- Krazee-eyez killah -- Mary, Joseph and Larry -- The grand opening.
Features: U.S. Comedy Arts Festival Panel with the cast and crew.
Larry David, Cheryl Hines, Jeff Garlin.
Originally broadcast on television in 2004.
MPAA rating: R.
DVDs, Dolby digital.
With English or French tracks and optional English, French, or Spanish subtitles.
Keywords: Television comedy writers -- Drama; Video recordings for the hearing impaired; Television programs; Comedy television programs